THE RECONSTRUCTION OF THE MAHAR TRADITION IN NORTH ACEH FROM THE PERSPECTIVE OF MAQĀSID AL-SYARĪ‘AH: THE DIALECTIC BETWEEN CUSTOMARY LAW AND ISLAMIC LAW - Miswanda Miswanda; Muhammad Syahrial Razali; Safriadi (STAI Nusantara Kota Banda Aceh, 2026)
This study examines the tradition of dowry in North Aceh through the perspective of maqāsid al-syarī‘ah by focusing on the interaction between local customs and Islamic family law. The issue of dowry in Acehnese society has undergone significant transformation due to social, cultural, and economic changes that often influence the implementation of marriage. In some cases, the amount of dowry is considered burdensome and has implications for delaying marriage among young people. This research aims to analyze the values of maslahat contained in the dowry tradition and reconstruct its implementation according to the objectives of Islamic law. This study employs qualitative research with a socio-normative approach. Data were obtained through literature studies, documentation, and analysis of Islamic legal sources, including classical and contemporary literature related to maqāsid al-syarī‘ah. The findings reveal that the dowry tradition in North Aceh fundamentally contains noble values such as respect for women, family dignity, and social responsibility. However, the shift in social orientation has transformed dowry into a symbol of prestige and social status. From the perspective of maqāṣid al-syarī‘ah, dowry should prioritize the principles of ease, justice, benefit, and protection of family welfare. Therefore, reconstruction of the dowry tradition is needed by emphasizing moderation, local wisdom, and the substantive values of Islamic law so that the implementation of marriage remains aligned with the objectives of the Sharī‘ah.